Dying for a paycheck how modern management harms employee health and company performance--and what we can do about it - Jeffrey Pfeffer (Holland, Ohio Dreamscape Media, 2018)
"In this timely, provocative book, Jeffrey Pfeffer contends that many modern management commonalities such as long hours, work-family conflict, and economic insecurity are toxic to employees--hurting engagement, increasing turnover, and destroying people's physical and emotional health--while also being inimical to company performance. He argues that human sustainability should be as important as environmental stewardship. You don't have to do a physically dangerous job to confront a health-destroying, possibly life-threatening workplace....In "Dying for a Paycheck", Jeffrey Pfeffer marshals a vast trove of evidence and numerous examples from all over the world to expose the infuriating truth about modern work life: even as organizations allow management practices that actually sicken and kill their employees, those policies do not enhance productivity or the bottom line, thereby creating a lose-lose situation. Exploring a range of important topics, including layoffs, health insurance, work-family conflict, work hours, job autonomy, and why people remain in toxic environments, Pfeffer offers guidance and practical solutions that all of us--employees, employers, and the government--can use to enhance workplace well-being. We must wake up to the dangers and enormous costs to today's workplace, Pfeffer argues. "Dying for a Paycheck" is a clarion call for a social movement focused on human sustainability. Pfeffer makes clear that the environment we work in is just as important as the one we live in, and with this urgent book he opens our eyes and shows how we can make our workplaces healthier and better."--jacket flaps
Keywords: Job stress